Computational Thinking: Students’ Abstraction on the Concepts of Kinematics - Rif'ati Dina Handayani; Sri Handono Budi Prastowo; Trapsilo Prihandono; Lailatul Nuraini; Bambang Supriadi; Maryani Maryani; Singgih Bektiarso; Albertus Djoko Lesmono Lesmono; I Ketut Mahardika (Postgraduate, University of Mataram, 2022)
Abstraction is the primary key in computational thinking. This study aims to analyze students’ computational thinking skills of abstraction on the concept of kinematics. The data were collected through students’ project documents and interviews. The data is examined using a content analysis approach that emphasizes writing, verbal, or visual communication. The results revealed that students’ abstraction skills were evident in collecting data and analyzing, and recognizing patterns but were less visible in building models or simulations. Abstraction skills can be used as a foundation and framework for viewing a concept in physics not only in mathematics or formulas views but as a data iterative relationship. This research is expected to provide an overview for physics instructors to integrate computational thinking in their learning classroom